The Factors Significantly affecting the Quality of Life of Patients Who undergo Radical Cystectomy due to Bladder Cancer - Chabowski, Mariusz; Juzwiszyn, Jan; Malinowska, Kamila; Kostka, Anna; Osmialowska, Edyta; Milan, Magdalena; Malinowski, Maciej; Janczak, Dariusz (Puerto Rico Health Sciences Journal, 2018)
Objective: Bladder cancer is, in Poland, the fourth most common malignancy in men and the eighth most common in women. Radical cystectomy often seems to be the only method of treatment. This mutilating procedure may affect the quality of life of the patient. The aim of our study was to analyze the impact of factors influencing quality of life in patients after a cystectomy. Methods: From January to August 2015, 50 consecutive patients treated in the Department of Urology of the Wroclaw Medical University in Wroclaw were enrolled into the study. Sixty-three percent of the respondents were men. Fifty-two percent of the respondents lived in urban areas. Patients ranged in age from under 25 to over 51 years. Clinical and demographic data were collected. Quality of life was evaluated with the SF-36 health survey questionnaire. For statistical analysis, Student’s t-test, the Mann–Whitney U test and Spearman’s rank correlation coefficient were used. Statistical analysis was carried out with IBM SPSS Statistics for Windows Version 21.0. Results: A decrease in quality of life was observed in both genders. The impact of place of residence on the occurrence of pain, health perception, vitality, and levels of physical and mental activity was found to be significant (p<0.05). Pain intensity, health perception, vitality, and levels of physical and mental activity were higher in patients living in urban areas. Conclusion: Patients with bladder cancer who underwent a radical cystectomy were more likely to have a reduced quality of life if they lived in a village or small town than if they lived in an urban area.